2006
DOI: 10.1002/jsfa.2554
|View full text |Cite
|
Sign up to set email alerts
|

Effect of drying conditions on bioactive compounds and antioxidant activity of broccoli (Brassica oleracea L.)

Abstract: The effect of air-drying parameters on antioxidant activity and changes in antioxidant compounds of broccoli (Brassica oleracea L.) were studied. Broccoli samples were dried to 70 g kg −1 moisture content using temperatures ranging from 50 to 100 • C and air flow-rates from 1.20 to 2.25 m s −1 , resulting in drying times from 25 to 90 min. Temperature, owing to its positive effect on the oxidation kinetics, was negatively correlated with ascorbic acid and free and total polyphenol contents but not with kaempfe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
90
0
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(97 citation statements)
references
References 55 publications
4
90
0
3
Order By: Relevance
“…Theauthors concluded that this phenomenon may be due to rapid drying initially favoring condensation reactions. Dther studies have shown that the drying rate is the most important factor in the preservation of a plant's phenolic compound content (Mrkìc et al, 2006).…”
Section: Resultsmentioning
confidence: 99%
“…Theauthors concluded that this phenomenon may be due to rapid drying initially favoring condensation reactions. Dther studies have shown that the drying rate is the most important factor in the preservation of a plant's phenolic compound content (Mrkìc et al, 2006).…”
Section: Resultsmentioning
confidence: 99%
“…Mrkic, Cocci, Dalla Rosa, and Sacchetti (2006) reported a higher antioxidant activity of air dried (50-100 °C, 25-90 min) broccoli with respect to the fresh vegetable. The authors explained this result by hypothesizing that there was an increase in compounds released from the matrix, hydrolytic phenomena during drying and polyphenol oxidation that resulted in oligomers with higher antioxidant activity than the native compounds.…”
Section: Antioxidant Activity In Fresh and Dried Murtilla Fruit By Dpmentioning
confidence: 95%
“…For example, high temperatures led to a lower level of the fl avonoid kaempferol in broccoli (Mrkic et al, 2006). Pan et al (2004) reported a progressive reduction in the anthocyanin content in strawberry fruits at temperatures ranging from 30 to 45 °C, and they suggested that this reduction is responsible for the onset of oxidative damage.…”
Section: Discussionmentioning
confidence: 99%